Solving the Closed-End Fund Puzzle in Vietnam: An Examination of Investor Sentiment and Fund's Liquidity - Phan, Le Hoang Mai (2011)
This paper examines the impact of stock liquidity and investor sentiment on premiums/discounts of closed-end funds in Vietnam. There are currently five funds listed on the Ho Chi Minh City Stock Exchange. They were issued at premiums and later traded at discounts to their net asset values. The investor sentiment hypothesis proposes that discounts on various funds move together. Closed-end funds and small stocks tend to be held by individual investors, and thus there should be a correlation between discount and small stock. The liquidity theory implies that funds with higher liquidity have higher premiums (lower discounts) than funds with lower liquidity. Liquidity is measured as proxies for trading activity. To test the investor sentiment theory, I follow the methodology of Lee, Thaler and Shleifer (1991) and investigate co-movements in discounts and small stocks, using the Pearson product-moment correlation measure. I also follow the work of Bennett and Gronewoller (2002) and carry out a co-integration analysis to examine whether there is a long and stable relationship between discount and proxies for investor sentiment. Then I use the methodology of Datar (2001) and run cross-sectional regressions on discounts/premiums against various proxies for liquidity. Overall, I find mixed results, and discounts are partially, but not fully, explained by the investor sentiment and liquidity theories.